2020
DOI: 10.1051/0004-6361/201937322
|View full text |Cite
|
Sign up to set email alerts
|

Average motion of emerging solar active region polarities

Abstract: Context. The tilt of solar active regions described by Joy’s law is essential for converting a toroidal field to a poloidal field in Babcock-Leighton dynamo models. In thin flux tube models the Coriolis force causes what we observe as Joy’s law, acting on east-west flows as they rise towards the surface. Aims. Our goal is to measure the evolution of the average tilt angle of hundreds of active regions as they emerge, so that we can constrain the origins of Joy’s law. Methods. We measured the tilt angle of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…These observation results are in general agreement with those of Kosovichev and Stenflo (2008). However, Schunker et al (2020) found it is still surprising that the active regions emerge with an east-west alignment since the thin flux tube model predicts a systematic tilt angle has developed at the apex of the emerging loop. With a simple model calculation (Apendix C Schunker et al 2020), they found that the observed average north-south separation motion of the polarities during the emergence is not consistent with an emerging loop with an initial constant tilt at the apex.…”
Section: Active Region Tiltssupporting
confidence: 87%
See 2 more Smart Citations
“…These observation results are in general agreement with those of Kosovichev and Stenflo (2008). However, Schunker et al (2020) found it is still surprising that the active regions emerge with an east-west alignment since the thin flux tube model predicts a systematic tilt angle has developed at the apex of the emerging loop. With a simple model calculation (Apendix C Schunker et al 2020), they found that the observed average north-south separation motion of the polarities during the emergence is not consistent with an emerging loop with an initial constant tilt at the apex.…”
Section: Active Region Tiltssupporting
confidence: 87%
“…Using the line-of-sight magnetograms from the Helioseismic and Magnetic Imager (HMI) on the Solar Dynamic Observatory (SDO), Schunker et al (2020) have measured the evolution of the tilt angles of 153 emerging active regions. It is found that for the beginning phase (Phase 1) of the flux emergence (during which the polarity separation speed is increasing, lasting about 0.5 days after the time of emergence), the active region polarities are on average east-west aligned with a zero mean tilt angle.…”
Section: Active Region Tiltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The converging flow toward the center of the active region as well as the prograde flow at the position of the leading polarity around the time of emergence are both present in all four subsamples. Joy's law is clearly visible after emergence, consistent with Schunker et al (2020), who showed that active regions on average emerge east-west aligned, and that Joy's law becomes evident two days after emergence. The tilt angle increases toward the higher-latitude subsamples and in time.…”
Section: Flows As a Function Of Time And Latitudesupporting
confidence: 86%
“…During the emergence of active regions, their magnetic polarities move apart, and develop a tilt angle, with the leading polarity closer to the equator than the trailing polarity (e.g. Schunker et al 2020, for a review see van Driel-Gesztelyi & Green 2015). This is consistent with the footpoints of the flux being connected to the subsurface field, and separating due to the action of magnetic tension and drag force (Chen et al 2017;Schunker et al 2019).…”
Section: Introductionmentioning
confidence: 63%